Menggali Potensi Kreativitas Dan Inovasi: Peran Pendidikan Karakter Di MTS Miftahus Sudur Campor Proppo - Nisrochah Hayati; Nur Amaliyah; Ria Kasanova (Universitas 45 Surabaya, 2023)
This study discusses the important role of character education in exploring the potential for creativity and innovation at MTs Miftahus Sudur Campor Proppo. Character education plays a key role in shaping moral values, positive attitudes, and ethics which form the basis for individuals to optimally develop creativity and innovation. In this research, several important aspects involving character education are analyzed in developing the potential for creativity and innovation. Things such as building ethical and moral foundations, developing an open attitude and critical thinking, strengthening independence and initiative, encouraging collaboration and cooperation, overcoming fear, and integrating imagination and problem solving are the main focus in understanding the role of character education in developing potential creativity and innovation. . This research provides valuable insight into how character education can be an effective tool in creating a supportive environment and facilitating the development of creative and innovative individuals.